Analisis Rugi-rugi Daya Listrik Akibat Ketidak Seimbangan Tegangan Penyulang Pada Motor Induksi Tiga Fasa Rotor Sangkar - Sularto, Hendry (ELKHA: Jurnal Teknik Elektro, 2012)
Abstract Unbalanced Voltage supply is case which is impossible to be avoided and inflict losses on. Unbalanced voltage is depended on line voltage unbalanced factor. Raising unbalanced factor will increase power losses and decrease efficiency of the three-phase induction motor. According to experiment result in laboratory, the increasing power loses is 58,47% and decreasing eficiency is 14,14% if motor operating in 5,0% unbalanced voltage factor, while theoretically computation results in the increasing of power losses is 241,79% and decreasing efficiency is 31,34% Keywords Unbalanced voltage, Motor, Losses